Skrining Fitokimia, Antibakteri, dan Antioksidan Ekstrak Etil Asetat Daun Puring (Codiaeum variegatum) - Ni Wayan Putri Primayanthi; Anak Agung Gede Indraningrat; Putu Arya Suryanditha (Aesculapius Medical Journal, 2025)
Bacterial infection is a condition where pathogens enter the body. Although bacterial infections are generally treated with antibiotics, the irrational use of antibiotics has triggered bacterial resistance. One effort to overcome bacterial infections can be done by exploring herbal plants that have antibacterial potential and other potentials, such as antioxidants. One herbal plant that needs further research is croton leaves (Codiaeum variegatum). The first stage in the research was maceration and extraction of croton leaves with ethyl acetate solvent, then carrying out phytochemical screening. Next, the antibacterial test used the Kirby-Bauer method with six treatments: positive control (levofloxacin), negative control (ethyl acetate), and croton extract concentrations, namely 100%, 75%, 50%, and 25%. The bacteria used were Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Streptococcus mutans FNCC 0405, and Klebsiella pneumoniae ATCC 700603. Antioxidant activity was tested using the DPPH method. The results of the phytochemical and antioxidant tests were analyzed descriptively, while the results of the antibacterial tests were analyzed using one-way ANOVA (for data with normal distribution) and Kruskal-Wallis (data which was not normally distributed). Phytochemical screening results show that croton leaf extract contains flavonoid compounds, tannins and phenols. The antibacterial test on croton leaf extract is classified as moderate to strong. At a concentration of 100%, the inhibition zone was found to be 11.8 ± 16.68 mm; 11.7 ± 0.87 mm; 12.23±0.23 mm; and 7.37 ± 0.69 mm respectively against Staphylococcus aureus ATCC 25923, Streptococcus mutans FNCC 0405, Klebsiella pneumoniae ATCC 700603, and Escherichia coli ATCC 25922. Antioxidant tests showed that croton leaf extract had a weak antioxidant (IC50 479.37 ppm). In general, this research shows that ethyl acetate extract of croton leaves has antibacterial potential in vitro. Future research should focus on testing ethyl acetate extract against multidrug-resistant bacteria and exploring other potential bioactivities of croton plants.